Curcumin triggers reactive oxygen species-mediated apoptosis and suppresses tumor growth in metastatic oral squamous cell carcinoma - Ramos, Tarsila de Carvalho Freitas; Dias, Rosane Borges; Santos, Luciano de Souza; Valverde, Ludmila de Faro; Nogueira, Raphael Luís Rocha; Bastos, Iasmin Nogueira; Coletta, Ricardo Della; Soares, Milena Botelho Pereira; Souza, Bruno Solano de Freitas; Santos, Jean Nunes dos; Reis, Mitermayer Galvão dos; Bezerra, Daniel Pereira; et al. (Frontiers in Oncology, 2025)
BackgroundOral squamous cell carcinoma (OSCC) remains a major clinical challenge with limited effective treatment options. In this context, several natural compounds (NC), such as curcumin, have shown promising effects in OSCC. However, there is still limited evidence about curcumin’s effects on cell death in metastatic OSCC cells and its cytotoxicity in preclinical models. To address this gap, this study aimed to evaluate the effects of curcumin on mitochondrial stress–induced apoptotic cell death and its cytotoxicity in preclinical models.MethodsCurcumin’s cytotoxicity was assessed in both 2D (monolayer) and 3D (spheroid model) cell cultures using a luminescent assay. Additionally, morphological parameters (FSC and SSC), apoptosis, and reactive oxygen species (ROS) production were analyzed in 2D cell cultures by flow cytometry, while morphological changes were evaluated in 3D cultures through microscopy. The in vivo assay was performed using a xenograft model in mice (C.B-17 SCID).ResultsCurcumin demonstrated cytotoxicity in 2D cell cultures, induced apoptosis, and increased ROS production, effects that were confirmed with antioxidant pretreatment (N-acetyl-L-cysteine). In the 3D cell culture, curcumin caused loss of spheroid integrity, suppressed tumor growth, and reduced tumor emboli and metastatic nodules in mice.ConclusionOur findings suggest that curcumin induces cell death via apoptosis mediated by oxidative stress and exhibits promising cytotoxic activity in the spheroid model, while also inhibiting OSCC growth in mice.